Molten‐Salt‐Assisted Synthesis of Bismuth Nanosheets for Long‐term Continuous Electrocatalytic Conversion of CO2 to Formate. (28th August 2020) - Yi, Luocai; Chen, Junxiang; Shao, Ping; Huang, Junheng; Peng, Xinxin; Li, Junwei; Wang, Genxiang; Zhang, Chi; Wen, Zhenhai
Abstract: Two‐dimensional (2D) monometallic pnictogens (antimony or Sb, and bismuth or Bi) nanosheets demonstrate potential in a variety of fields, including quantum devices, catalysis, biomedicine and energy, because of their unique physical, chemical, electronic and optical properties. However, the development of general and high‐efficiency preparative routes toward high‐quality pnictogen nanosheets is challenging. A general method involving a molten‐salt‐assisted aluminothermic reduction process is reported for the synthesis of Sb and Bi nanosheets in high yields (>90 %). Electrocatalytic CO2 reduction was investigated on the Bi nanosheets, and high catalytic selectively to formate was demonstrated with a considerable current density at a low overpotential and an impressive stability. Bi nanosheets continuously convert CO2 into formate in a flow cell operating for one month, with a yield rate of 787.5 mmol cm −2  h −1 . Theoretical results suggest that the edge sites of Bi are far more active than the terrace sites. Abstract : A low‐temperature molten‐salt‐assisted method to synthesize nanosheet‐like monometallic antimony or bismuth with high‐yield has been developed. The obtained bismuth nanosheets can effectively and continuously electrocatalyze the reduction of CO2 to formate with a stability of more than one month.